(untitled) (International Journal of Engineering Materials and Manufacture, 2022)
Conduction heat transfer in gaps containing many porous objects has not been widely discussed, despite several applications. This study aims to determine the mechanism and calculate conduction heat transfer in porous objects and whether there is a change in the thermal conductivity value. The research started from a mathematical model with a horizontal medium, and the results were matched with the simulation results. Porous objects contain water that can evaporate. This study used clove buds stacked with a certain thickness which caused porous between the piles of cloves. So, this research uses several heat transfer formulas related to porous media. The new formula is obtained to get the thickness of cloves pile based on the amount of porosity of objects and the porosity between the piles of objects.